PENGARUH AKUNTANSI BERBASIS SAK EMKM TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Empiris Pada UMKM di Kabupaten Pasuruan) - Achmad Nursalim; Maslichah Maslichah; Junaidi Junaidi (Universitas Islam Malang, 2019)
ABSTRACTThe financial statements presented by SMEs are still limited to information on cash receipts and disbursements and the absence of personal account separators with business accounts. The purpose of this study was to determine the effect of EMKM SAK-based accounting on the quality of SME financial statements. The data used in this study are primary data. The number of MSME registered in the cooperatives and UKM in Pasuruan Regency is 248,802. to get the research sample used Slovin formula, so that the sample was 99.9 and fulfilled to 100 respondents. The sampling technique is done using the random sampling method. The results obtained using a simple linear regression test Y = 8.432 + 0.970X + ϵ, and the test from this study also used the t-test. The results of the t-test show that EMKM-based SAK accounting has a positive effect on the quality of financial statements.Keywords: Accounting, SAK EMKM, and Financial Report Quality